Intrauterine diagnosed sternal cleft patient and her management - YÜKSEL, MUSTAFA (My University, 2016)
Sternal cleft is a rare chest wall deformity. It can be diagnosed in the intrauterine stage with ultrasonography. Newborn period is the optimal time for the surgical correction of sternal cleft, due to the elasticity of the sternum and minimal compression of underlying structures. Here we reported a newborn patient with sternal cleft which has been operated 5 days after labor. Good surgical outcome and long-term results were accomplished.
Keywords: Congenital abnormalities; intrauterine diagnosis; sternal cleft; surgical correction